Biotic Factors Responsible for Damage of Khamer (Gmelina arborea) Plantations in Central India - Verma, R. K.; Meshram, P. B. (Indian Forester, 2019)
Biotic factors including insect pests, fungi and animals responsible for damage in the plantations of Gmelina arborea were identified and reported from central India. Nearly 30 per cent trees were recorded healthy with no infection while rest 70 per cent trees showed low to heavy infestation (37.2% trees showed low infestation, 22.1% medium and 11.3% showed heavy infestation) at different sites in Chhattisgarh and Madhya Pradesh states. Insects identified were, Indarbela quadrinotata, Tingis beesoni, leaf miner (Phyllochistis sp.), Eupterote germinata, Selepa celtis, Hapalia aureolalis, Dihammus cervinus, Sahyadrassus (Phassus) malabaricus, Alcidodes gmelinae, Odontotermes obesus and Hieroglyphus banian. Eight associated fungi namely, Ganoderma lucidum, Epicoccum nigrum, Flavodon flavus, Hexagonia tenuis, Hypoxylon rubigenosum, Leptosphaeria gmelinae, Nattrassia mangiferae and Pseudocercospora ranjita were also identified. Among these bark eating insect, Indarbela quadrinotata occurred most frequently and damaged the plantations. Nattrassia mangiferae (=Hendersonula toruloidea) causing canker on main stem was found the most damaging amongst fungi reported. Some animals like monkeys, goats, small deer and porcupine also damaged the plantations in some areas.